Dealing with Governance and Anticorruption Issues in Fragile and Conflict-Affected States : Ten Things Team Leaders Should Know - World Bank (Washington, DC, 2013)
Over the past several years, to improve development outcomes, the Bank has developed new and more effective tools and approaches for dealing with governance and anticorruption (GAC) issues at the country, sector, and project levels. At the same time, the Bank has increased its focus on fragile and conflict-affected states (FCS), as reflected in the 2011 World Development Report (WDR): conflict, security, and development. Helping these countries achieve their development objectives, including the Millennium Development Goals (MDGs), is a critical part of the Bank s mission to reduce poverty. On a parallel track, the Bank is working to strengthen its support to the FCS. The approach includes both near-term policy and procedural changes to improve the Bank s operational effectiveness, and the preparation of a more comprehensive strategy for longer-term engagement, building on the analysis and recommendations of the 2011 WDR. In attempting to integrate the GAC and FCS agendas, it is clear that we have much to learn. For example, that governance and corruption risks pose a serious threat in many of the FCS, not just to the achievement of development objectives but to the prospects for sustaining peace and building more accountable state institutions. However, emerging good practice GAC tools and approaches may not work in FCS, or at least they will need to be adapted to FCS circumstances. This note aims to share what authors have learned so far about some of the practical things that task team leaders (TTLs) should take into account in designing and supervising Bank-financed projects in FCS.